Digital Literacy Among EFL Teachers: Navigating Technological Demands in 21st-Century Classrooms - Nur Ifadloh; Adebayo Sherifat Shola; Afifah Afifah (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2025)
This study investigates the digital literacy of English as a Foreign Language (EFL) teachers and the challenges and support systems they encounter in integrating technology into 21st-century classrooms. Drawing on qualitative data from semi-structured interviews and classroom observations with seven EFL teachers, the research explores the multidimensional nature of teachers' digital literacy, the systemic and emotional obstacles they face, and the informal strategies they adopt to cope. The findings reveal that digital literacy among EFL teachers extends beyond technical skill to include pedagogical adaptability and critical awareness. However, limitations such as infrastructural instability, lack of institutional guidance, and emotional resistance often hinder full digital engagement. Despite these challenges, teachers demonstrate agency by forming peer support networks, engaging in self-directed learning, and drawing encouragement from student feedback. These informal mechanisms, while valuable, highlight the absence of coordinated institutional support. The study concludes that sustainable digital integration in EFL contexts requires a holistic approach that combines technological access, emotional support, and professional learning communities. By reframing digital literacy as a dynamic and context-sensitive practice, the study contributes to ongoing dialogues around teacher agency, equity, and innovation in language education.